Navigating the intussusception scoring system: A journey beyond boundaries - Siahaan, Tarida Christio Ersanna Onlia; Hariastawa, IGB Adria; Matulatan, Fendy (Edelweiss Applied Science and Technology, 2025)
Bowel resection is usually performed in the operative management of pediatric intussusception patients when the strangulation process lasts for a long time, causing intestinal ischemia and necrosis. A combined scoring system of biological markers and clinical conditions of pediatric patients with intussusception can be a tool to help make decisions to perform appropriate and rapid intestinal resection to reduce patient morbidity and mortality. This was a retrospective cross-sectional study of pediatric intussusception patients undergoing laparotomy surgery at Dr. Soetomo Hospital in 2019 – 2024. The data were collected from electronic medical records, with 69 patients meeting the inclusion criteria, multivariate analysis was performed to obtain markers and ratios of inflammatory markers associated with the occurrence of intestinal necrosis in pediatric patients with intussusception. Of the total 69 subjects, 49 (58%) underwent bowel resection and the rest (29 [42%]) resolves without bowel resection, 49 (58%) was male and dominated by age group of < 12 months old (51 [73,9%]), the most common clinical symptoms was abdominal pain (68 of 69 [98,6%]). Using the Backward Stepwise method, 2 clinical factors were obtained in the form of significant vomiting and abdominal mass (p < 0.05) and a biological marker in the form of CAR cut off (p < 0.05). Conclusion: A scoring system could not be created in this study, but several variables could be used as components of a scoring system in the future study.